Penerapan Grammar Translation Method (GTM) dalam Pembelajaran Bahasa Inggris Peserta Didik Di SD Negeri 2 Sungai Mempura - Lulu Dwivinanti; Anna Humaira (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
KUKERTA are student service activities to the community. Service activities can be carried out by distributing knowledge that students have obtained to the community. Sungai Mempura is one of the villages in the Siak Regency. Sungai Mempura has one public elementary school, namely SD Negeri 2 Mempura. SD Negeri 2 Mempura still lacks teaching staff or teachers, one of which is an English teacher. The English language skills of SD Negeri 2 students are pretty worrying. Sungai Mempura is one of the tourist villages that local and foreign tourists often visit. This underlies the Kukerta team holding grammar-based learning because it is the primary thing these students need. The method we use is a grammar-based word translation method. The results obtained during this activity are that many students still lack English language skills, but their interest in learning English is relatively high. This can be seen from the students' enthusiasm during the teaching activities. Thus, it is hoped that this grammar-based teaching activity can improve the abilities and interests of the students of SD 2 Mempura.